WAVE EQUATIONS FOR GRAVIMAGNETIC FIELD - Abdildin, M. M. (Recent Contributions to Physics, 2009)
Wave equations for potentials of gravimagnetic field in nonstationary case in general relativity were obtained in this work.
Keywords: Wave equations